Collision tumour of ovary: a rare combination of fibrothecoma with serous cystadenoma - Mishra, Archana; Shamsunder, Saritha; Malik, Sunita; Zaheer, Sufian (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
A collision tumour is defined by presence of two separate tumors in one organ on gross, microscopic and immune-histochemical studies without any admixture. These tumors are reported from oesophagus, stomach, liver, lung and thyroid glands. Such tumors are extremely rare in ovary. In case of ovaries most common histological collision reported between mucinous tumors and teratomas. We are reporting a rare combination of fibrothecoma with serous cystadenoma in right ovary of a premenopausal woman. Both gynaecologist and pathologist should be aware of such combination. It is important to differentiate such tumors from malignant ovarian tumors. Frozen section and scrape cytology are important tools which help in appropriate management of such cases intraoperatively.